Prevalence of musculoskeletal disorder and its association with risk factors among vehicle service technicians in Klang Valley, Malaysia - Ahmad Nasaruddin, Ahmad Faisal (2016)
Introduction: The primary objective of this study is to determine the association between risk factors and the prevalence of Musculoskeletal Disorder (MSD) among vehicle technicians in Klang Valley, Malaysia. Methodology: This cross-sectional study was conducted at eight vehicle service centers in Klang Valley, Malaysia. One hundred and ninety one technicians were recruited. A modified version of the general Standardised Nordic Questionnaire was used for analyses of perceived MSD in nine different parts of the body (neck, shoulder, elbow, arms, upper back, lower back, thigh, knee and legs). Rapid Upper Limb Assessment (RULA) test had been done to determine the work posture of the respondent and hand vibration had been measured. Independent Chi-square test was used to determine the significant association between MSD prevalence and the risk factors. Binary logistic regression was performed to assess the association between risk factors on the MSD prevalence. The probability limits for evaluating statistical significance was p < 0.05. Results: The prevalence of MSD among vehicle service technicians is 82.7% and suffered from MSD especially on body parts which are shoulder 62.3%, legs 61.8%, neck 59.2% and lower back 56 %. The logistic regression shows significant association between MSDs and job demand OR=3.713 (95% C.I.=1.121-12.290, p=0.012). BMI and monthly income also show significant association with OR=4.661 (95% C.I.=1.204-18.030, p=0.025) and OR=4.770 (95% C.I.=1.393-16.330, p=0.012) respectively. Conclusion: Service technicians at vehicle service centers in Klang Valley are likely to be exposed to a variety of ergonomic hazards and risk factors. Therefore, ergonomics awareness among employer and employee with training and information sharing shall be increase to reduce the prevalence of MSDs.